Practitioner experience with sonic osteotomy compared to bur and ultrasonic saw: a pilot in vitro study. Issue 2 (February 2015) - Rashad, A.; Sadr-Eshkevari, P.; Heiland, M.; Smeets, R.; Prochnow, N.; Hoffmann, E.; Maurer, P.
Abstract The aim of the present study was to compare subjective experiences using bur, ultrasonic, and sonic osteotomy systems. Ten novice (N) and 10 expert (E) practitioners performed osteotomies on bovine ribs with each system. They scored ease of handling and sense of accuracy on visual analogue scales. The duration of the osteotomy procedure and the amount of noise were recorded objectively. Learning experience was evaluated in a second run. The Mann–Whitney U-test, Wilcoxon signed rank tests, and Spearman's rank correlation coefficient were used for the statistical analyses. The sonic system was significantly slower, with the worst noise impact (92.9 dB; standard deviation (SD) 7.1). However, both user groups improved significantly in the second run (N 7.9, E 7.6). There were no significant differences in handling. The sense of accuracy was evaluated to be significantly best for the sonic system (N 8.4, E 8.4), compared to the ultrasonic system (N 7.1, E 7.1; both P = 0.043) and bur system (N 5.5, P = 0.002; E 6.0, P = 0.006). The practitioners had a promising experience with the application of the ultrasonic system and particularly with the sonic system.